2023
DOI: 10.1136/bmjopen-2023-072855
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intervention to increase uptake of voluntary medical male circumcision among men with sexually transmitted infections in Malawi: a preinterventional and postinterventional study

Mitch M Matoga,
Evaristar Kudowa,
Beatrice Ndalama
et al.

Abstract: ObjectiveTo evaluate the effect a multistrategy demand-creation and linkage intervention on voluntary medical male circumcision (VMMC) uptake, time to VMMC and predictors of VMMC uptake among men with sexually transmitted infections (STIs).DesignPragmatic preinterventional and postinterventional quasi-experimental study combined with a prospective observational design.SettingA public and specialised STI clinic in Lilongwe, Malawi.PopulationUncircumcised men who presented to the STI clinic.Methods and intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The primary trial was a pragmatic pre- and post-interventional quasi- experimental study that measured baseline VMMC uptake and prospectively observed uncircumcised men with STIs for 30 days after implementation exposure for uptake of circumcision in Lilongwe, Malawi. The study demonstrated a 100% increase in VMMC uptake between the pre- and post-intervention periods [15]. The intervention was rolled-out in a sequential and incremental manner called implementation blocks.…”
Section: Methodsmentioning
confidence: 99%
“…The primary trial was a pragmatic pre- and post-interventional quasi- experimental study that measured baseline VMMC uptake and prospectively observed uncircumcised men with STIs for 30 days after implementation exposure for uptake of circumcision in Lilongwe, Malawi. The study demonstrated a 100% increase in VMMC uptake between the pre- and post-intervention periods [15]. The intervention was rolled-out in a sequential and incremental manner called implementation blocks.…”
Section: Methodsmentioning
confidence: 99%